Suspected chikungunya outbreak in Klungkung, Bali: Environmental and behavioral risk factors - Ni Luh Rahayu Widaryati; Ni Putu Widarini; Putu Dwi Adi (Science Midwifery, 2026)
Chikungunya outbreaks in communities with no prior recorded transmission history remain poorly studied in Indonesia, where delayed case detection and low community health literacy present distinct epidemiological challenges. This study investigated a suspected chikungunya extraordinary event in Banjar Jumpai Kangin, Desa Jumpai, Kabupaten Klungkung, Bali, between April and May 2025, with the aim of describing the epidemiological characteristics of the outbreak and identifying the environmental and behavioral risk factors associated with transmission. A case-control design was employed, with data collected through structured interviews, direct environmental observation, and secondary data review. A total of 36 suspected cases were identified, peaking at 8 cases on 8 May 2025, with the majority being female (58.3%) and aged 5 to 14 years (33.3%). All cases presented with fever (100%), followed by arthralgia (91.7%) and rash (83.3%). Bivariate analysis identified four significant risk factors, including the absence of routine water storage container draining (p less than 0.001), the absence of mosquito nest eradication practices (p = 0.046), the presence of mosquito larvae in the household (p = 0.032), and the lack of personal protective behavior against mosquito bites (p = 0.018). Community knowledge of chikungunya was uniformly poor across both case and control groups. Delayed case reporting substantially prolonged the period before any public health response was initiated. These findings underscore the need for proactive community-based surveillance in areas with no prior chikungunya history, and support policy interventions targeting household vector control practices and health literacy as the primary levers for outbreak prevention.